2003
DOI: 10.1159/000074515
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Retardation and Consequences for Endocrine and Cardiovascular Diseases in Adult Life: Does Insulin-Like Growth Factor-I Play a Role?

Abstract: Low birth weight has been associated with an increased incidence of ischaemic heart disease (IHD) and type 2 diabetes. Endocrine regulation of fetal growth by growth hormone (GH) and insulin-like growth factor (IGF)-I is complex. Placental GH is detectable in maternal serum from the 8th to the 12th gestational week, and rises gradually during pregnancy where it replaces pituitary GH in the maternal circulation. The rise in placental GH may explain the pregnancy-induced rise in maternal serum IGF-I levels. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 159 publications
(195 reference statements)
0
33
0
Order By: Relevance
“…In cattle, the IGF-I, IGF-II and insulin receptor concentrations were shown to decrease throughout foetal development from 3 to 5 months of age onwards in both the skeletal muscle (Boge et al, 1995;Listrat et al, 1999b) and the heart (Hocquette et al, 2006 for IGF-I and insulin receptors only). In various mammals, increase in IGF-I (Jensen et al, 2003 for humans) and IGF-II plasma levels (Listrat et al, 1999a for cattle) were observed throughout gestation. Therefore, the IGF-I, IGF-II and insulin receptor levels are the lowest at the end of gestation when the IGF-I levels in foetuses are the highest, when foetal glucose level is the lowest and when foetal GLUT4 expression increases (Hocquette et al, 2006).…”
Section: Endocrine and Metabolic Regulation Of Muscle Physiology Befomentioning
confidence: 99%
“…In cattle, the IGF-I, IGF-II and insulin receptor concentrations were shown to decrease throughout foetal development from 3 to 5 months of age onwards in both the skeletal muscle (Boge et al, 1995;Listrat et al, 1999b) and the heart (Hocquette et al, 2006 for IGF-I and insulin receptors only). In various mammals, increase in IGF-I (Jensen et al, 2003 for humans) and IGF-II plasma levels (Listrat et al, 1999a for cattle) were observed throughout gestation. Therefore, the IGF-I, IGF-II and insulin receptor levels are the lowest at the end of gestation when the IGF-I levels in foetuses are the highest, when foetal glucose level is the lowest and when foetal GLUT4 expression increases (Hocquette et al, 2006).…”
Section: Endocrine and Metabolic Regulation Of Muscle Physiology Befomentioning
confidence: 99%
“…IGF-1 gene was shown to · contain a Variable Number of Tandem Repeats (VNTR) in the promoter region and IGFBP3 gene a single nucleotide polymorphism (SNP) (A_, C) at position -202 in the promoter region. [15][16][17][18][19][20] If some controversy exists on the association between IGF-1 VNTR and JGF-1 s'erum values, most studies showed a significant reduction of IGF-1 concentrations in non-carriers of the most common allele, 19CA [16][17][18][19][20]. IGFBP3 SNP was shown to correlate with adult IGFBP3 serum concentrations, the mutated C allele being associated with decreased circulating concentrations [21,22].…”
Section: Resu/tsmentioning
confidence: 99%
“…Assuming a similar trend for the hormonal status in humans and cattle i.e. an increase in IGF-I levels throughout gestation [4] and taking into account the increase in IGF-II plasma levels with increasing age in foetal cattle [53], IGF-I, IGF-II and insulin receptor levels would be low at those stages where IGF-I and placental GH levels in pregnant females and IGF-I levels in foetuses are the highest [4], when foetal glucose level is the lowest and when foetal GLUT4 expression increases (present study). Furthermore, other in vitro studies with cultured cells from the rat hindlimb during differentiation have shown that GLUT1 is abundant in myoblasts, whereas GLUT4 is expressed in spontaneously contracting myotubes but absent in myoblasts [10].…”
Section: Overall Differentiation Of the Heart And Adipose Tissuementioning
confidence: 99%
“…For the heart, cardiovascular diseases may also be partly programmed during intrauterine growth [1,3]. Furthermore, low birth weight has been associated with an increased incidence of ischemia [4] or cardiovascular diseases [5]. The challenge is, nowadays, to understand the basic biological mechanisms which control tissue differentiation and how they are regulated by nutritional factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation